(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This research work is aimed at interpreting the airborne magnetic data of the study area for mapping the basement geologic structures using magnetic image enhancement filters. It focus on performing filtering techniques to expose and identify the magnetic properties of the basement structures at various continuation distances. The procedure applied to Total Magnetic Intensity (TMI) data of the study area using Oasis MontanjTM software were Reduction to Magnetic Equator (RTME) to remove the inclination effect as well as positioning the peak of the anomalies over their sources so as to improve the orientation of the magnetic sources, separation of regional and residual magnetic anomalies. These was followed by application of upward continuation at 500 m, 1000 m, 2000 m and 3000 m height. The results of the RTME shows the amplitude of the magnetic anomalies ranging from -37.577 nT to 27.398 nT. High magnetic anomaly is dominated in the northwest, southeast through southern part of the study location. Furthermore the results of the Upward Continuation (UC) revealed a wider wavenumber anomalies as well as height above the near surface. Hence the results of this research has displayed an enhanced geological magnetic structures located in the study area and also shows an improved quality of magnetic anomalies as the continuation distances increases.